(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
Bahuvrihi compounds, first described in the grammatical tradition of Sanskrit by Pāṇini, represent one of the most intriguing types of exocentric word-formation. In such compounds, the meaning of the whole expression does not correspond directly to its constituents but refers instead to an external entity. This structural peculiarity has drawn attention in many linguistic traditions; however, the stylistic and metaphorical dimensions of bahuvrihis remain insufficiently explored. The present paper offers a comparative investigation of English and Uzbek bahuvrihi compounds, focusing on their stylistic registers, metaphorical domains, and evaluative orientations. English bahuvrihis, such as redhead, bigmouth, and bookworm, tend to emerge in colloquial discourse, where they function with humorous, ironic, or figurative force. By contrast, Uzbek bahuvrihis, including vatanparvar (“patriot”), ilmparvar (“science-loving”), and foydaxor (“profit-seeker”), reveal a systematic tendency to encode ideological, moral, and cultural values through productive affixoid patterns like –parvar, –go‘y, and –xor. Beyond their formal and semantic characteristics, bahuvrihis are shown to operate as semiotic reflections of cultural worldview. The English tradition highlights individual traits and satirical perspectives, while the Uzbek tradition foregrounds collective identity and ethical ideals. This contrast demonstrates how compounding, as a universal wordformation process, can serve radically different cultural functions across languages. The analysis is based on a balanced dataset of 60 compounds (30 English, 30 Uzbek) drawn from lexicographic, descriptive, and corpus-based sources. The findings suggest that English bahuvrihis are predominantly negative or ironic in orientation, whereas Uzbek bahuvrihis favor positive and ideologically elevated evaluations. By integrating morphological typology, cognitive metaphor theory, and cultural linguistics, the study argues that bahuvrihi compounds provide valuable insight into how language encodes cultural salience, ideological orientation, and social identity. Ultimately, the paper contributes to comparative linguistics and cognitive semantics by demonstrating that bahuvrihi compounds are not marginal curiosities of morphology but meaningful cultural signs. Their analysis opens pathways for future corpus-driven, diachronic, and interdisciplinary research that could trace how compounding practices evolve in response to changing cultural and communicative needs.